But could they tell right from wrong? Evolution, moral responsibility and human distinctiveness - Field, David (HTS teologiese studies, 2017)
This article takes as its point of departure the public interest aroused by the discovery of Homo naledi and the debate about the possibility that H. naledi buried their dead. If they buried their dead, did H. naledi have an awareness of moral responsibility? We have no basis in the fossil remains of H. naledi or other hominids for determining when and how the awareness of moral responsibility evolved. The article provides a brief summary of the evidence for the evolution of morality based on research into the behaviour of other primates and then argues that human moral consciousness is qualitatively distinct from this but can still be understood to be the product of evolution. In the final section the article draws on ideas from the theologies of John Wesley and Dietrich Bonhoeffer to provide a theological interpretation of this evolution of moral consciousness.